Insulin resistance factors associated with differentiated thyroid carcinoma and malignant cytology: serum thyroxine as an associated factor - Lina Guzikauskas Celescuekci; Mariana Pereira Pinto; Ilka Mara Borges Botelho; Elizabeth João Pavin; Denise Engelbrecht Zantut-Wittmann (Annals of Medicine, 2025)
Background Factors related to cardiovascular risk and insulin sensitivity seem to be related to the increase in the number of thyroid cancer (TC) diagnosis, but there is a lack of studies to corroborate these hypotheses.Methods This observational and cross-sectional study evaluated ultrasonographic, clinical, cytological and anatomopathological characteristics of thyroid nodules (TN) related with factors indicative of cardiovascular risk (CVR), serum lipids, and glucose profiles through medical records, and interviews during routine medical consultation.Results The study included 160 TN patients, 85.53% women, 41.3% with obesity, 24.18% with type 2 Diabetes Mellitus, 63.4% with arterial hypertension, 9.15% with previous CVR, 38.16% with dyslipidemia. 38.5% had Papillary TC, 8.5% Follicular TC. Regarding cytology categories (Bethesda,B), 34.64% BII, 8.5% BIII, 11.11% BIV, 26.8% BV, 8.5% BVI. Microcalcifications were associated with higher Framingham and ASCVD CVR Scores, fasting glucose and glycated hemoglobin. BII TN had lower fasting glucose; BIII greater glycated hemoglobin; and BIV higher both CVR scores. Framingham Score was lower in papillary TC, abdominal waist was lower in follicular TC. Higher FT4 increased 4.7 times the chance of malignant cytology. Higher HDL was an associated factor for malignant cytology (OR = 1.064) and higher FT4 for Differentiated TC (OR = 7.409).Conclusion TN with greater malignant potential on ultrasound and cytology were associated with greater CVR and altered glucose metabolism. Larger goiters and multiple nodules were related to factors indicative of insulin resistance. Malignant cytology was related to hormonal factors that induce greater cell replication, such as thyroxine and insulin resistance.